ENVIRONMENTAL SUSTAINABILITY INDICATORS FOR UNIVERSITIES - Šereš, Laslo; Tumbas, Pere; Matković, Predrag (International Journal of Economic Practice and Policy, 2020)
Over the past two decades, many universities have engaged and included the concept of sustainable development into their academic systems. Numerous declarations and charters have been signed and initiatives accepted, providing universities with guidelines or frameworks, and also showing their dedication to include the aspect of sustainability into their business systems. All of this, however, does not secure their successful implementation. To attain a higher responsibility level at universities, it is generally necessary to perform monitoring or assessment of sustainable development. After the introductory considerations, this paper briefly elaborates the most frequently used types of metrics in sustainability assessment. Available results of completed empiric research into sustainable development at 15 universities worldwide, published in separate reports on sustainable development or general annual reports were collected from web pages. These were used for identification, analysis and systematization of sustainability indicators at universities. Only environmental sustainability indicators were chosen as object of detailed observation. Five primary groups of indicators have been established and certain suggestions for future actions have been made, which need to be implemented at universities to attain better sustainable development results at universities in the short run.